The mouse who saved Egypt - Alrawi, Karim; Wiley, Bee (Northampton, Mass. : Crocodile Books, 2011)
In ancient times, a young Egyptian prince rescues a mouse and many years later, when the boy has become Pharoah, the mouse hears his prayer to the Sun God and finds a way to repay the debt.
2.0
K-3
K-3
Keywords: Folklore -- Egypt; Folklore -- Egypt; Folklore -- Egypt; Picture books for children